Colonic hiatal hernia leading to obstruction after minimally invasive McKeown esophagectomy: a case report - Ma, Danyang; Wang, Jiang; Li, Tong; Pang, Mingyuan; Lu, Hengxiao (Frontiers in Surgery, 2025)
A 62-year-old man presented with acute abdominal pain and signs of bowel obstruction eight months after undergoing a minimally invasive McKeown esophagectomy for esophageal squamous-cell carcinoma. Initial imaging did not reveal a hernia, and conservative management was unsuccessful. Re-evaluation of imaging suggested a hiatal hernia, and thoracoscopic exploration confirmed a large hernia with the transverse colon herniating into the thoracic cavity. Surgical repair involved reduction of the herniated colon and repair of the diaphragmatic hiatus. The patient recovered uneventfully. This case highlights the diagnostic challenges of post-esophagectomy hiatal hernias and the importance of prompt surgical intervention.